Gender in cardiovascular medicine: chest pain and coronary artery disease. (12th November 2019) - Mehta, Puja K; Bess, Courtney; Elias-Smale, Suzette; Vaccarino, Viola; Quyyumi, Arshed; Pepine, Carl J; Bairey Merz, C Noel
Abstract: Ischaemic heart disease (IHD) remains the leading cause of morbidity and mortality among women and men yet women are more often underdiagnosed, have a delay in diagnosis, and/or receive suboptimal treatment. An implicit gender-bias with regard to lack of recognition of sex-related differences in presentation of IHD may, in part, explain these differences in women compared with men. Indeed, existing knowledge demonstrates that angina does not commonly relate to obstructive coronary artery disease (CAD). Emerging knowledge supports an inclusive approach to chest pain symptoms in women, as well as a more thoughtful consideration of percutaneous coronary intervention for angina in stable obstructive CAD, to avoid chasing our tails. Emerging knowledge regarding the cardiac autonomic nervous system and visceral pain pathways in patients with and without obstructive CAD offers explanatory mechanisms for angina. Interdisciplinary investigation approaches that involve cardiologists, biobehavioural specialists, and anaesthesia/pain specialists to improve angina treatment should be pursued.